Association between gout and kidney stone: results from mendelian randomization and the NHANES study - Jin, Shengkai; Geng, Haochen; Lu, Yichen; Zhou, Yuhua; Lv, Jing; Fu, Chaowei; Zhang, Yuwei; Li, Menglu; Feng, Ninghan (Frontiers in Genetics, 2024)
BACKGROUND Kidney stones are a common urologic disease with an increasing incidence year by year, and there are similar influences between gout status and kidney stone incidence. Therefore the contribution of gout status to the incidence of kidney stones is unclear. The aim of this study was to investigate the relationship between gout status and kidney stones and to further explore the causal relationship by Mendelian randomization (MR) analysis.An epidemiologic study of 49,693 participants in the 2009-2018 National Health and Nutrition Examination Survey (NHANES) was conducted to examine the association between the two. The causal relationship between gout status and kidney stones was assessed by Mendelian randomization analysis of data from the GWAS database.RESULT A total of 28742 participants were included in the NHANES analysis.We found that gout status was associated with an increased risk of kidney stones [odds ratio (OR) = 1.45 (95%CI, 1.243-1.692); P < 0.001]. In the MR analysis, we found a causal relationship between gout status and the risk of developing kidney stones (OR = 1.047, 95%CI, 1.011-1.085, P = 0.009). CONCLUDE There may be an association between gout status and kidney stone risk. This finding requires further large-sample studies and adequate follow-up.